PD-1/PD-L1 Inhibitor-Associated Myocarditis: Epidemiology, Characteristics, Diagnosis, Treatment, and Potential Mechanism - Dong, Hao; Qi, Yihang; Kong, Xiangyi; Wang, Zhongzhao; Fang, Yi; Wang, Jing (Frontiers in Pharmacology, 2022)
Immune checkpoint inhibitors (ICIs) induce T-cell activation against cancer cells, and due to their anti-tumor function in multiple cancers, ICIs have been considered an important option for oncotherapy. PD-1/PD-L1 inhibitors are now widely used ICIs for many kinds of cancers in clinical practices. Myocarditis induced by anti PD-1/PD-L1 agents is an uncommon, but potentially fatal toxicity. In this review, we attempted to conclude the incidence, characteristics, diagnosis and treatments, as well as illustrate the potential pathogenesis from the perspectives of T lymphocytes infiltration, disturbance of regulatory T cells, cytokines, macrophages mediated inflammatory response and synergistic effect of PD-1/PD-L1 and CTLA-4.